ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KOMITMEN ORGANISASIONAL PEGAWAI BADAN PUSAT STATISTIK WILAYAH PROVINSI PAPUA - Due G. B. Sihombing; Westim Ratang; Zulkifli Sultan (JURNAL ILMIAH EDUNOMIKA, 2024)
The role of the Central Statistics Agency is very dependent on the human resources working in the agency. Employees must have good expertise and skills. This work requires high professionalism and integrity, because the data produced must be accurate and trustworthy. The purpose of this research is to investigate the influence of work-family conflict, workload and compensation on job satisfaction and its implications for employee organizational commitment. Questionnaires were used as a data collection technique obtained from BPS employees in the Papua Province region with a final sample of 203 people. The sampling technique is probability sampling with an area sampling approach. Data were analyzed using the SEM (Structural Equation Modeling) technique. The research results show that work-family conflict and compensation have a significant effect on job satisfaction, but workload does not have a significant effect on job satisfaction. Apart from that, compensation and job satisfaction have a significant effect on organizational commitment. However, work-family conflict and workload do not have a significant effect on organizational commitment. The final results show that job satisfaction mediates the effect of compensation on organizational commitment.